2019
DOI: 10.1101/781781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CK2-dependent phosphorylation of the Brg1 chromatin remodeling enzyme occurs during mitosis

Abstract: Brg1 (Brahma related gene 1) is one of two mutually exclusive ATPases that can act as the catalytic subunit of mammalian SWI/SNF chromatin remodeling enzymes that facilitate utilization of the DNA in eukaryotic cells. Brg1 is a phospho-protein and its activity is regulated by specific kinases and phosphatases. Previously, we showed that Brg1 interacts with and is phosphorylated by casein kinase 2 (CK2) in a manner that regulates myoblast proliferation.Here we demonstrate that the Brg1-CK2 interaction occurred … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Thus, the obtained high amount of CX-4945 in the nuclear fraction may be responsible for its high impact on apoptosis induction. Recently, an interaction of CK2 and the chromatin remodeling enzyme Brg1 within the nucleus of proliferating myoblasts was observed [64]. Since this interaction takes place in the nucleus, the high amount of CX-4945 in this fraction could be explanatory for its strong anti-proliferative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the obtained high amount of CX-4945 in the nuclear fraction may be responsible for its high impact on apoptosis induction. Recently, an interaction of CK2 and the chromatin remodeling enzyme Brg1 within the nucleus of proliferating myoblasts was observed [64]. Since this interaction takes place in the nucleus, the high amount of CX-4945 in this fraction could be explanatory for its strong anti-proliferative effects.…”
Section: Discussionmentioning
confidence: 99%
“…BRG1 has been shown to be phosphorylated during mitosis, which correlates with its dissociation from condensed chromatin and inactivation (Muchardt et al, 1996;Sif et al, 1998). Recent studies showed that Casein kinase 2 phosphorylates BRG1 during mitosis at multiple sites, and that these phosphorylation events are important for myoblast proliferation and survival (Padilla-Benavides et al, 2020;Padilla-Benavides et al, 2017). During myogenesis, phosphorylation of BRG1 by PKCβ1 and dephosphorylation by calcineurin regulates gene expression (Nasipak et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of transcription regulators influences a dynamic protein interaction network that allows neurons to produce rapid and diverse responses to enable adaption to the changing environment. Despite the identification of phosphorylation sites in BAF subunits in various conditions (Kimura et al, 2014;Kwon et al, 2015;Padilla-Benavides et al, 2020;Wang et al, 2013), it is not clear whether BAF subunits undergo protein modifications in response to neuron activities or how posttranslational modifications regulate BAF activities.…”
Section: Introductionmentioning
confidence: 99%